2009
DOI: 10.1111/j.1582-4934.2009.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential for control of detrusor smooth muscle spontaneous rhythmic contraction by cyclooxygenase products released by interstitial cells of Cajal

Abstract: Interstitial cells of Cajal (ICCs) have been identified as pacemaker cells in the upper urinary tract and urethra, but the role of ICCs in the bladder remains to be determined. We tested the hypotheses that ICCs express cyclooxygenase (COX), and that COX products (prostaglandins), are the cause of spontaneous rhythmic contraction (SRC) of isolated strips of rabbit bladder free of urothelium. SRC was abolished by 10 μM indomethacin and ibuprofen (non-selective COX inhibitors). SRC was concentration-dependently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 75 publications
0
40
0
Order By: Relevance
“…The present study has shown that PGE 2 augments spontaneous basal MCs observed in isolated rat urinary bladder strips as observed in many other species such as guinea pig (De Jong et al 2007), rabbit (Collins et al 2009) and mouse (Kobayter et al 2012). …”
mentioning
confidence: 49%
“…The present study has shown that PGE 2 augments spontaneous basal MCs observed in isolated rat urinary bladder strips as observed in many other species such as guinea pig (De Jong et al 2007), rabbit (Collins et al 2009) and mouse (Kobayter et al 2012). …”
mentioning
confidence: 49%
“…9E). We recently showed that spontaneous rhythmic contraction in DSM can be abolished by cyclooxygenase inhibitors, suggesting that prostaglandins are basally released by detrusor (6). Thus, prostaglandin receptor activation may rather selectively activate cell signaling systems involved in regulating APS.…”
Section: Discussionmentioning
confidence: 99%
“…28 It has been suggested that ICs may have a pivotal role as so-called pacemakers and mediators of neurotransmission in the bladder, urethra and penile erectile tissue. [14][15][16][17]29 The role of ICs in the clitoris remains to be established. Some hypotheses have been proposed: adult mesenchymal cells, which might participate in (a) intercellular signaling or (b) chemo-mechanical transducing or act as (c) players in pace-making through direct cell-to-cell communication.…”
Section: Discussionmentioning
confidence: 99%